Analisis Pengaruh Kualitas Produk, Kualitas Pelayanan, Desain Produk, Harga Produk Dan Kepercayaan Terhadap Loyalitas Pelanggan Indosat Im3 Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta - Arum Dewanto, Febry; , Jati Waskito S.E., M.Si (2015)
Febry Arum, Scholar Program, Muhammadiyah University of Surakarta, Analyzis Influence of Product Quality, Service Quality, Product Design, Product Price and Trust To Customer's Loyality. This research purposes: 1) To analysis influence product quality to customer's loyality of IM3 product 2) To analysis influence service quality to customer's loyality of IM3 product 3) To analysis influence product design to customer's loyality of IM3 product 4) To analysis influence product price to customer's loyality of IM3 product 5) To analysis influence trust to customer's loyality of IM3 product This research uses primary data. Sample of this research uses 100 respondents caome from students of Economic Faculty by Bussiness Muhammadiyah University of Surakarta. Technique collecting sample uses purposive sampling or collecting sample by random with certain criterion. Criterion is students active in Economic Faculty and Bussiness of Muhammadiyah University of Surakarta who are still or user of IM3 card. Analysis method uses regression linier with validity and reliability test before, assumsi classic uses normality, multicolinierity and heteroscedasticity tests. Hyphotesis test uses simultant significance test (F-test) and significant partial test (t-test) and adjusted R square with standard error of estimate using 5% or 0.05. Result of this research 1) base on analysis result regression linier of this research Y = Y = -1,821 + 0,282 X1 + 0,248 X2 + 0,267 X3 + 0,137 X4 + 0,270 X5; 2) Result of this research from answer index shows product quality (X1) has index value 76.8 that highest score and product quality has most influence of analysis regression 0.282 where result of this research from respondent's perception by fiture or special added of IM3 product is fulfull needed of customer so effort customer's loyality IM3 in Economic and business faculty of Muhammadiyah University of Surakarta. Product quality variable (X1) has positive influence and significant to customer's loyality (Y) with regression value 0.282 and tvalue = 3.619 with significant 0.000 3) Result of research and answer index shows service quality variable has index value 79.5 high score level where result of research by respondent's perception measure almost respondent said service quality IM3 positive and significant to customer's loyality (Y) with regression 0.248 and t value = 3.436 with significant 0.004. 4) Result of this research answer index of respondent shows product design variable (X3) has index value 79.4 that high score level where result of research by respondent perception measure said product design IM3 is interest. Design product (X3) has positif and significant to customer's loyality (Y) with regession value 0.267 t value = 3.261 with significant value 0.006 5) Result of research and answer index shows price (X4) has index value 80.3 high score level where result of research by respondent's perception measure almost respondent said price IM3 appropriate with special fiture, reaching and appropriate with value of money. Price variable (X4) has positive and significant to customer's loyality (Y) with regression value 0.137 and tvalue = 2.170 with significant level 0.033; 6) result of research from answer index 79.3 that is high score level where result of research respondent's perception value almost respondent said IM3 is satisfaction so effort customer's loyality of IM3. Trust (X5) has positive and significant to customer's loyality (Y) with regression value 0.370 and t value = 3.240 with significant level 0.002 7) From result of regression test known product quality variable (X1) has dominant influence to customer's loyality (Y) with regression value 0.282, while price variable (X4) has smallest influence to customer's loyality (Y) is regression value is 0.137. This shows product offer with expensive price customer still buy product because certain reason quality product. It means product popular in quality so, how much money spent of customer it is no problem. It is evident if customer important of quality product (X1) than price (X4). Keyword: customer loyality, product quality, service quality, design product, price product and trust.